Competitiveness of the Ghanaian vegetable sector: Findings from a farmer survey - van Asselt, Joanna; Masias, Ian; Kolavalli, Shashidhara (International Food Policy Research Institute, 2018)
This study looks broadly at the state of vegetable competitiveness in Ghana; focusing on trade, production, profitability, and marketing. Ghana is dependent on imports to meet its vegetable consumption requirements. While Ghana has the potential to meet local vegetable demand because of its diverse agro-ecological zones, currently production is highly seasonal and yields are significantly lower than in neighboring countries. Large urban markets are restricted by networks of traders and, while farmers can get higher prices through these networks, many farmers lack market power and struggle to access the marketing networks. This may lower incentives for vegetable farmers to increase their production. However, despite these challenges, vegetable production is profitable and there is potential for significant expansion. Strategies to improve yields as well as measures to remove restrictions on entry to major markets should be considered.